One Hundred Years of the Communist Party Influencing the Islamic World - Ridha, Muhammad (UI Scholars Hub, 2024)
The ideology of Communism has had a significant impact on Muslim-majority countries in the Middle East, North Africa, Central Asia and Southeast Asia. The emergence of Communist parties has triggered prolonged social and political tensions and changed the power dynamics in Muslim countries.